THE ROLE OF MEDIEVAL EASTERN ART MASTERPIECES IN THE DEVELOPMENT OF OUR NATIONAL CULTURE. - Xaztarova Zilola Shavkat qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The most ancient ideas about the role and importance of the masterpieces of art of the Asian peoples in the Middle Ages in the development of our national culture are presented and include the VIII-XVII centuries.